Inoculation of Azospirillum brasilense associated with silicon as a liming source to improve nitrogen fertilization in wheat crops - Galindo, Fernando Shintate [UNESP]; Buzetti, Salatiér [UNESP]; Rodrigues, Willian Lima [UNESP]; Boleta, Eduardo Henrique Marcandalli [UNESP]; Silva, Vinicius Martins [UNESP]; Tavanti, Renan Francisco Rimoldi [UNESP]; Fernandes, Guilherme Carlos [UNESP]; Biagini, Antônio Leonardo Campos [UNESP]; Rosa, Poliana Aparecida Leonel [UNESP]; Teixeira Filho, Marcelo Carvalho Minhoto [UNESP] (Springer Nature, 2020)
This research was developed to investigate whether inoculation with Azospirillum brasilense in combination with silicon (Si) can enhance N use efficiency (NUE) in wheat and to evaluate and correlate nutritional and productive components and wheat grain yield. The study was carried out on a Rhodic Hapludox under a no-till system with a completely randomized block design with four replications in a 2 × 2 × 5 factorial scheme: two liming sources (with Ca and Mg silicate as the Si source and limestone); two inoculations (control - without inoculation and seed inoculation with A. brasilense) and five side-dress N rates (0, 50, 100, 150 and 200 kg ha−1). The results of this study showed positive improvements in wheat growth production parameters, NUE and grain yield as a function of inoculation associated with N rates. Inoculation can complement and optimize N fertilization, even with high N application rates. The potential benefits of Si use were less evident; however, the use of Si can favour N absorption, even when associated with A. brasilense. Therefore, studies conducted under tropical conditions with Ca and Mg silicate are necessary to better understand the role of Si applied alone or in combination with growth-promoting bacteria such as A. brasilense.